2016
DOI: 10.1007/s00430-016-0487-5
|View full text |Cite
|
Sign up to set email alerts
|

Gender and age-specific seroprevalence of human papillomavirus 16 and 18 in general population in Tehran, Iran

Abstract: The assessment of the gender and age-specific seroprevalence of human papillomavirus (HPV) is essential for planning of HPV vaccine implementation into the preventive programs. In this study, we aimed to determine the age-specific seroprevalence of HPV-16 and 18 in both males and females in Tehran, Iran. Three hundred and seventy-eight women (10-35 years) and 162 men (10-25 years) from Tehran, Iran, were enrolled. Anti-HPV IgG antibodies against HPV-16 and HPV-18 were detected by ELISA using papillomavirus typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…However, in Aghakhani et al HPV infection was more often found in an older age group. HPV‐16 antibody was detected in 15.6% and 13.6% of women and men, respectively, being the highest HPV‐16 and 18 seroprevalence seen in women aged 26‐30 years and the lowest seropositivity seen in males and females aged 10‐15 years.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, in Aghakhani et al HPV infection was more often found in an older age group. HPV‐16 antibody was detected in 15.6% and 13.6% of women and men, respectively, being the highest HPV‐16 and 18 seroprevalence seen in women aged 26‐30 years and the lowest seropositivity seen in males and females aged 10‐15 years.…”
Section: Discussionmentioning
confidence: 89%
“…HPV infection is the most common sexually transmitted infection in the world. 23 The incidence of HPV-associated diseases, such as squamous cell carcinomas, has increased in children in recent years which may be, in part, related to an increase in HPV prevalence in parents. 24 HPV infection rates and distribution of different HPV types are known to vary significantly in different countries and regions.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of antibodies to HPV E7, Hsp20, Hsp27 proteins and Hp91 peptide was determined in 49 serum samples from Iranian women who were seropositive for HPV-16 and 18 L1 capsids [34] as well as controls. The mean absorbance values for rE7, rHsp20, rHsp27 proteins and Hp91 peptide in HPV-16-exposed women were 1.083 ± 0.390, 0.455 ± 0.284, 0.873 ± 0.374 and 0.338 ± 0.329, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Serum samples were collected from 49 Iranian women (with no previous treatment, vaccination and immunodeficiency disorders) who were seropositive for HPV-16 (22 cases, group 1), HPV-18 (12 cases, group 2) and both HPV-16 and 18 (15 cases, group 3) L1 capsids as observed in our previous study (Additional file 1, Ref. [34]) and 49 control women. All the subjects were recruited from outpatients attending to hospitals in Tehran, Iran, for routine checkup or mild diseases such as common cold; 34).…”
Section: Methodsmentioning
confidence: 99%
“…Some authors argue that the prevalence of HPV infection is associated with age, and hence with the pattern of sexual behaviour in the community. Thus, HPV prevalence is greater at earlier ages (15–25 years) with the initiation of sexual intercourse; later, between 25–40 years of age, there is a marked decrease, after which the prevalence stabilises [ 34 ]. However, the percentage of persistence among those aged 25–40 years is higher, which implies an increased risk of pre-neoplastic lesions, due to the above-mentioned trend in this age group [ 35 ].…”
Section: Discussionmentioning
confidence: 99%